SPE International Conference on Health, Safety, and Environment in Oil and Gas Exploration and Production 1998
DOI: 10.2118/46578-ms
|View full text |Cite
|
Sign up to set email alerts
|

Dilution and Bioavailability of Produced Water Compounds in the Northern North Sea. A Combined Modeling and Field Study

Abstract: A combined field and modeling study addressing the dilution and spreading of produced water originating polycyclic aromatic hydrocarbons (PAH) has been carried out in the Tampen region, located in the Norwegian sector of the Northern North Sea. Sampling sites were identified in the region and located in positions near production platforms and in open sea. The station network was designed to cover areas in open sea. The station network was designed to cover areas in open sea. The station network was designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Field studies conducted with fish, mussels, and passive samplers in cages have shown that it is possible to detect an increased uptake of PAHs and APs up to several kilometres from the platform Durell et al, 2006;Johnsen and Røe, 1998;Tollefsen et al, 2005;Harman et al, 2009). Biomarker analyses have also shown that fish held in cages close to the PW discharge outlet show a small but detectable induction of Vtg and CYP1A (King et al, 2005;Scott et al, 2006a;Zhu et al, 2008).…”
Section: Environmental Implications Of Our Results Compared To the Simentioning
confidence: 99%
“…Field studies conducted with fish, mussels, and passive samplers in cages have shown that it is possible to detect an increased uptake of PAHs and APs up to several kilometres from the platform Durell et al, 2006;Johnsen and Røe, 1998;Tollefsen et al, 2005;Harman et al, 2009). Biomarker analyses have also shown that fish held in cages close to the PW discharge outlet show a small but detectable induction of Vtg and CYP1A (King et al, 2005;Scott et al, 2006a;Zhu et al, 2008).…”
Section: Environmental Implications Of Our Results Compared To the Simentioning
confidence: 99%
“…Several studies have been performed to monitor and model the fate and effects of produced water discharges to the Norwegian sector of the North Sea (Durell et al, 2000(Durell et al, , 2004Johnsen et al, 1998;Neff et al, 2006;. These studies were designed partly to serve as baseline studies for future monitoring programs, and partly to evaluate, optimize, and implement different sampling, monitoring, and assessment techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The paper is not intended to in detail describe the sampling techniques used to generate the field-based data, or discuss the merits and drawbacks of those methods (such information has been presented in other papers by these and other authors). The data from two field studies are described in this paper: a survey in the Tampen Region in 1997 (Johnsen et al, 1998; and one in the Ekofisk Region in 1999 (Durell et al, 2000). A companion paper (Neff et al, 2006) compares the ecological risk predicted based on these field measurements to risk predicted using DREAM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study served as the basis for developing the official Norwegian strategy for monitoring ecological risks of produced water discharges from offshore production facilities to water column communities. The results of the Tampen monitoring study have been summarized in several papers (Johnsen et al, 1998;. Durell et al (2004) and Durell et al (2000) described the field monitoring programs and summarized the results of the Ekofisk monitoring study.…”
Section: Introductionmentioning
confidence: 99%